SWOT Analysis and Strategy Mapping in Accelerating the Adoption of Generative AI in Indonesian SMEs - Irawan, Risky (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The rapid development of generative artificial intelligence (AI) presents significant opportunities for small and medium-sized enterprises (SMEs) in Indonesia to enhance innovation, operational efficiency, and competitiveness. However, adoption remains limited due to constraints in human capital, financial capacity, and digital infrastructure. This study aims to identify the strategic factors influencing generative AI adoption among Indonesian SMEs and to design a framework that accelerates its implementation using SWOT analysis and strategy mapping. Employing a qualitative literature review method, the research synthesizes findings from academic and institutional sources published between 2018 and 2025. The results reveal that Indonesian SMEs possess notable strengths, including entrepreneurial agility and growing digital literacy, yet face weaknesses such as limited AI expertise and investment capacity. Opportunities arise from supportive national policies, affordable cloud technologies, and collaborative ecosystems, while threats include cybersecurity issues and regulatory uncertainty. Through strategy mapping based on the Balanced Scorecard framework, four perspectives—learning and growth, internal process, customer, and financial—are connected to guide AI adoption strategically. The study proposes actionable recommendations for SME managers, policymakers, and supporting institutions to build capability, governance, and collaboration. Overall, this research provides a comprehensive strategic model to facilitate effective and sustainable generative AI adoption among Indonesian SMEs.